Effect of electrolytes as adjuvants in GFP and LPS partitioning on aqueous two-phase systems: 1. Polymer-polymer systems - Lopes, André Moreni [UNESP] (2018)
The production of recombinant biopharmaceuticals is highly dependent of a proper choice of the downstream processing stages. Particularly, the purification that must ensure that all the endotoxins (lipopolysaccharides - LPS) are efficiently removed from the final product. The efficient removal of LPS has a direct impact on the manufacturing of therapeutic biopharmaceuticals, since LPS is naturally presented in Gram-negative bacterial expression systems. In order to provide a more simple and faster technique for the purification of green fluorescent protein (GFP) and LPS removal, aqueous two-phase systems (ATPS) composed of polyethylene glycol (PEG) and poly(acrylic acid) (NaPA) and electrolytes were studied. Firstly, the binodal curves of PEG/NaPA + salt systems were established using NaCl, Li2SO4, KI, and KNO3 as additives. It was demonstrated that the formation of ATPS is enhanced following the anion tendency: SO4 2− > Cl− ≫ NO3 − > I−. The stability of GFP in the presence of all different phase forming agents (polymers and salts) was evaluated, and the high biocompatibility of these ATPS demonstrated by the maintenance of GFP fluorescence in all conditions under study. Then, the GFP extraction and LPS removal aptitude of each ATPS was investigated. GFP and LPS were preferentially partitioned into the top (PEG-rich) phase (KGFP > 20), but with a removal of 35% of LPS was attained. Hydrophobic and electrostatic interactions were found to be the major driving forces for GFP partitioning and LPS removal. Moreover, a new effect was found, the presence of high loads of LPS can affect (decrease) the KGFP values (KGFP without LPS > KGFP with 104 EU/mL > KGFP with 106 EU/mL). The ATPS with best GFP extraction performance was selected for the recovery directly from the cell lysates of Escherichia coli. In this experiment, the system composed of 12 wt% PEG 1000 g/mol, 12 wt% NaPA 8000 g/mol, and 0.25 M Li2SO4 lead to a LPS removal (REMLPS) of 13%, KGFP of 20.2, and high selectivity relatively to the total proteins (S = 20), since the majority of contaminants proteins were preferentially partitioned into the bottom (NaPA-rich) phase (purification factor of 4-fold). It is here demonstrated that the ATPS composed of PEG/NaPA + salts as additives can be used as a first step for the recovery of GFP and removal of contaminants (LPS in part, and most contaminant proteins) from cell lysates by applying a system with low polymer content and using mild conditions.